Optimization of the fermentation media and growth conditions of Bacillus velezensis BHZ-29 using a Plackett–Burman design experiment combined with response surface methodology - Shi, YingWu; Niu, XinXiang; Yang, HongMei; Chu, Ming; Wang, Ning; Bao, HuiFang; Zhan, FaQiang; Yang, Rong; Lou, Kai (Frontiers in Microbiology, 2024)
The carbon and nitrogen sources, and inorganic salts that affect the number of viable bacteria and antibacterial potency of B. velezensis BHZ-29, were screened by a single factor test. A Plackett-Burman design experiment was conducted to determine the significant factors affecting the number of viable bacteria and antibacterial potency, and a Box-Behnken design experiment was used to obtain the optimal growth of B. velezensis BHZ-29. The medium formula that produced the highest number of viable bacteria and most antibacterial substances was determined. The initial pH, temperature, amount of inoculant, liquid volume, shaking speed, and culture time were determined by a single factor test. The factors that had a significant influence on the number of viable bacteria of B. velezensis BHZ-29 were selected by an orthogonal test. A Box-Behnken design experiment was conducted to obtain the optimal fermentation conditions, and highest number of viable bacteria and antibacterial titer. Molasses, peptone, and magnesium sulfate had significant effects on the viable count and antibacterial titer of B. velezensis BHZ-29. The viable count of B. velezensis BHZ-29 increased from 7.83 × 109 to 2.17 × 1010 CFU/mL, and the antibacterial titer increased from 111.67 to 153.13 mm/mL when the optimal media were used. The optimal fermentation conditions for B. velezensis BHZ-29 were as follows: temperature 25.57°C, pH 7.23, culture time 95.90 h, rotation speed 160 rpm, amount of inoculant 2%, and liquid volume 100 mL. After the optimization of fermentation conditions, the number of viable bacteria increased to 3.39 × 1010 CFU/mL, and the bacteriostatic titer increased to 158.85 mm/mL. The plant height and leaf number of cotton plants treated with BHZ-29 fermentation broth were higher than those of cotton inoculated with Verticillium dahliae.. The number of bacteria was 1.15 × 107 CFU/g, and the number of fungi was 1.60 × 105 spores/g. The best effect was achieved in the treatment group with an inoculation concentration of 2 × 108 CFU/mL, the disease index was 14.50, and a control effect of 84.18% was achieved.